2019
DOI: 10.3892/mmr.2019.10855
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor mediates the proliferation and glucose metabolism of pancreatic cancer cells via AKT pathway activation

Abstract: Pancreatic cancer (Pc) is the fourth leading cause of cancer-related mortality worldwide. leptin is an adipokine that is significantly increased in obese patients and that functions in various biological processes of cancer, such as tumor growth and metastasis. However, its role in Pc cell proliferation and glucose metabolism and the underlying mechanisms remain unclear. in the present study, in vitro leptin treatment significantly promoted cell proliferation and increased glucose uptake and lactate production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The fact that p53 is activated in the adipose tissue of obese animals, along with the results here presented concerning a putative direct role of p53 in controlling Upd2/ Leptin expression, demonstrates the importance of p53 in regulating metabolism. This is particularly interesting given that epidemiological studies over the last few decades have shown a strong influence of obesity on cancer risk and that increased Leptin can have hormone-like functions affecting tumor development (Andò et Singh et al, 2020;Xu et al, 2020). In this context, our results give insights toward the molecular understanding of p53 activation under metabolic stress and its possible role in tumor suppression acting at either local or organismal level.…”
Section: P53-dependent Leptin Regulation In Animal Physiology and Dismentioning
confidence: 68%
“…The fact that p53 is activated in the adipose tissue of obese animals, along with the results here presented concerning a putative direct role of p53 in controlling Upd2/ Leptin expression, demonstrates the importance of p53 in regulating metabolism. This is particularly interesting given that epidemiological studies over the last few decades have shown a strong influence of obesity on cancer risk and that increased Leptin can have hormone-like functions affecting tumor development (Andò et Singh et al, 2020;Xu et al, 2020). In this context, our results give insights toward the molecular understanding of p53 activation under metabolic stress and its possible role in tumor suppression acting at either local or organismal level.…”
Section: P53-dependent Leptin Regulation In Animal Physiology and Dismentioning
confidence: 68%
“…35,36 Recent studies showed that leptin receptor mediated the regulation of the glucose metabolism via activation of AKT pathway. 37 The AKT inhibitor can significantly counteracted the effect of leptin, and AKT activator can counteracted the effect of leptin silencing. In addition, galanin can benefit glucose uptake via inhibition of adenylyl cyclase and cAMP through Gi/o receptors to activate the PI3K/Akt signalling pathway too.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic hypoxia inducible factor (HIF)-1α was identified to bind directly to hypoxiaresponsive elements (HREs) located in the LEPR gene promoter (-828/-832), thereby activating downstream transcriptional events in pancreatic cancer cells, suggesting the potential significance of the leptin receptor-mediated axis during hypoxia [81]. In a study of pancreatic cancer, the results demonstrated that exogeneous leptin could enhance cell proliferation, glucose uptake and lactate production in a dose-dependent manner, and that this was accompanied by elevated expression of the glycolytic enzymes hexokinase II and glucose transporter 1, suggesting the potential involvement of glucose metabolism in pancreatic cancer progression [82]. In addition, simultaneously high leptin receptor and MMP13 production exhibited a positive correlation with TNM status in pancreatic cancer patients.…”
Section: Leptin and Pancreatic Cancermentioning
confidence: 95%
“…↑: [67,70] ↑: [67] ↓: [66] Lung Cancer ↑: [79,80] ↑: [76,77,80] ↑: (erlotinib) [78], (cisplatin) [79] Pancreatic Cancer ↑: [82,87,88] ↑: [83] ↑: (gemcitabine) [86], (5-FU) [87] Prostate Cancer ↑: [89] ↑: [89,90] ↓: [89] Gallbladder cancer ↑: [91] Myeloma ↑: (bortezomib) [92] Chondrosarcoma ↑: [93,94] ↑: increase.↓: decrease.…”
Section: Colorectal Cancermentioning
confidence: 99%